Genetic variation for grain protein components and industrial quality of durum wheat cultivars sown in Argentina - Lerner, S. E. (2004)
Eleven cultivars of durum wheat from Argentina and Chile were analysed for their endosperm storage protein allelic composition and for industrial quality characteristics. For the HMW glutenin subunits, all cultivars carried the null allele Glu-A1c, and four variants were observed at Glu-B1: Glu-B1b (encoding subunits 7+8), Glu-B1d (subunits 6+8), Glu-B1e (subunits 20+20y) and Glu-B1z (subunits 7+15). For the Glu-3 encoded B-LMW glutenin subunits, alleles Glu-A3a (subunit 6), Glu-A3b (subunit 5), Glu-B3a (subunits 2+4+15+19), Glu-B3b (8+9+13+16) and Glu-B3c (2+4+14+15+19) were observed, and for the Glu-B2 encoded B-LMW glutenin subunits, Glu-B2a (subunit 12) and Glu-B2b (null allele). A B-LMW glutenin subunit not previously reported was observed in the cultivar Buck Cristal and provisionally designated subunit 6.1. A wide range of values for the characters gluten index, SDS-sedimentation volume and the Farinograph parameters energy level and tolerance was obtained from grain harvested from field trials sown in Argentina. There were strong correlations between these characters, and less strong correlations with grain protein and gluten content. While some cultivars varied for quality performance between years, others were relatively consistent for both extremes of performance. The analyses suggested that the gene pool represented by the cultivars investigated comprises useful variation for future breeding programmes, and provides pointers for directions that such programmes could take.